2016
DOI: 10.1021/acs.biochem.6b00614
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Properties of the Aldehyde Dehydrogenase NahF, a Broad Substrate Specificity Enzyme for Aldehyde Oxidation

Abstract: The salicylaldehyde dehydrogenase (NahF) catalyzes the oxidation of salicylaldehyde to salicylate using NAD(+) as a cofactor, the last reaction of the upper degradation pathway of naphthalene in Pseudomonas putida G7. The naphthalene is an abundant and toxic compound in oil and has been used as a model for bioremediation studies. The steady-state kinetic parameters for oxidation of aliphatic or aromatic aldehydes catalyzed by 6xHis-NahF are presented. The 6xHis-NahF catalyzes the oxidation of aromatic aldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Many other ALDHs form the same tetramer, including ALDH1 [9][10][11][12], ALDH2 [13,14], ALDH5A1 [15], methylmalonate semialdehyde dehydrogenase [16], ALDH21 [17], 2-aminomuconate-6-semialdehyde dehydrogenase [18], betaine aldehyde dehydrogenase [19], lactaldehyde dehydrogenase [20], indole-3-acetaldehyde Abbreviations ALDH, aldehyde dehydrogenase; EM, electron microscopy; PDE, pyridoxine-dependent epilepsy; PLP, pyridoxal-5 0 -phosphate. dehydrogenase [21], a-ketoglutarate-semialdehyde dehydrogenase [22], propionaldehyde dehydrogenase [23], and salicylaldehyde dehydrogenase [24]. Further investigation of the in-solution oligomeric state of ALDH7A1 using analytical ultracentrifugation revealed a concentration-dependent dimer-tetramer equilibrium with a dissociation constant (K d ) of 16 lM [25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many other ALDHs form the same tetramer, including ALDH1 [9][10][11][12], ALDH2 [13,14], ALDH5A1 [15], methylmalonate semialdehyde dehydrogenase [16], ALDH21 [17], 2-aminomuconate-6-semialdehyde dehydrogenase [18], betaine aldehyde dehydrogenase [19], lactaldehyde dehydrogenase [20], indole-3-acetaldehyde Abbreviations ALDH, aldehyde dehydrogenase; EM, electron microscopy; PDE, pyridoxine-dependent epilepsy; PLP, pyridoxal-5 0 -phosphate. dehydrogenase [21], a-ketoglutarate-semialdehyde dehydrogenase [22], propionaldehyde dehydrogenase [23], and salicylaldehyde dehydrogenase [24]. Further investigation of the in-solution oligomeric state of ALDH7A1 using analytical ultracentrifugation revealed a concentration-dependent dimer-tetramer equilibrium with a dissociation constant (K d ) of 16 lM [25].…”
mentioning
confidence: 99%
“…Initial structural studies revealed ALDH7A1 forms a dimer‐of‐dimers tetramer both in crystallo and in solution . Many other ALDHs form the same tetramer, including ALDH1 , ALDH2 , ALDH5A1 , methylmalonate semialdehyde dehydrogenase , ALDH21 , 2‐aminomuconate‐6‐semialdehyde dehydrogenase , betaine aldehyde dehydrogenase , lactaldehyde dehydrogenase , indole‐3‐acetaldehyde dehydrogenase , α‐ketoglutarate‐semialdehyde dehydrogenase , propionaldehyde dehydrogenase , and salicylaldehyde dehydrogenase . Further investigation of the in‐solution oligomeric state of ALDH7A1 using analytical ultracentrifugation revealed a concentration‐dependent dimer–tetramer equilibrium with a dissociation constant ( K d ) of 16 μ m .…”
mentioning
confidence: 99%
“…In contrast to the better studied aromatic aldehyde dehydrogenases identified from various Pseudomonas species (55)(56)(57), which have been studied because of their ability to catabolize and biodegrade a range of compounds, including napthalene-derived molecules, and metabolic aldehyde dehydrogenases linked to the osmoprotectant betaine and growth in biofilms (58)(59)(60), less is understood about the biochemistry of aliphatic aldehyde dehydrogenases in these microbes. Here we comprehensively examined and identified AldC from PtoDC3000 as a long-chain aliphatic aldehyde dehydrogenase using an integrated approach combining phylogenetic, crystallographic, and biochemical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The aldehyde dehydrogenase from Corynebacterium glutamicum exists in dimeric, trimeric, and tetrameric forms, as revealed by gel filtration chromatography 44 . In the case of SAL dehydrogenase, SALDpp generated a dimeric biological unit, as shown by the determination of its crystal structure 45 . The enzyme from Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…SALDan was also determined to be trimeric based on gel filtration chromatography and protein cross-linking analyses. Despite having different modes of oligomerization, each monomer can be divided into three domains: a cofactor binding domain composed of a core that resembles the Rossmann fold, a catalytic α/β domain, and a small protruding domain that enables oligomerization 45 46 . The oligomerization domains of SALD are located in the β7, β21, and C-terminus regions ( Fig.…”
Section: Discussionmentioning
confidence: 99%